PTH-111 "non Celiac Gluten Sensitivity" (ncgs) Is Uncommon In Patients Spontaneously Adhering To Gluten Free Diet (gfd), And Is Outnumbered By "fodmaps Sensitivity". (9th June 2014) - Zanini, B; Baschè, R; Ferraresi, A; Lanzarotto, F; Marullo, M; Ricci, C; Lanzini, A
Abstract : Introduction: It is controversial whether symptoms in patients fulfilling the clinical criteria for NCGS 1 are specifically triggered by gluten or by cereal components other than gluten and specifically FODMAPs, or are attributable to a nocebo effect 2 . Our aim was to test assess gluten or FODMAPs dependence of symptoms in patients diagnosed as NCGS. Methods: NCGS patients referred to our Clinic were randomised to a double blind cross over study involving challenge with 10 g gluten Vs 10 g gluten free flour containing FODMAPs for 10 days each with 2 weeks wash-out in between (challenge stage). Patients were subsequently kept on a low FODMAPs diet for 8 weeks (low FODMAPs stage) Endpoints: patients were asked to indicate by symptom recurrence the gluten phase of challenge; correct identification was taken to indicate NCGS and incorrect identification accompanied by reduction of GSRS score during the low FODMAPs diet were taken to indicate FODMAPs sensitivity. Results: Twenty-five patients without celiac disease (age 42+9 years, M/F = 2/23, 10 HLA DQ2/8 positive, 13 negative, 2 unknown) on strict GFD entered the study. During the challenge stage, the gluten phase was correctly identified by 8 patients thus fulfilling criteria for NCGS (4 with HLA DQ2/8). Scores for the 3 dimensions of GSRS (pain p = 0.03; indigestion p = 0.02; and diarrhoea p = 0.02) were higher in NCGS patients during the gluten than gluten free flour challenge. Twelve patients thought they were challenged gluten while on gluten free flour indicating gluten independent symptom recurrence (gluten insensitive). GSRS scores in these patients were higher (pain p = 0.004; reflux p = 0.013; indigestion p = 0.014, constipation p = 0.014) during challenge with gluten free flour than with gluten. Five patients reported mild symptoms during both phases suggesting a nocebo effect. During the low FODMAPs stage the score of indigestion dimension (comprising borborygmus, bloating, eructation, flatus) was significantly reduced (p = 0.011) in the gluten insensitive patients suggesting FODMAPs sensitivity. There was no significant change in the 5 dimensions of the GSRS in NCGS patients. Conclusion: We conclude that the population of patients reporting intolerance to gluten containing diet is a mixed population of NCGS and of FODMAPs sensitive patients. NCGS is uncommon and is outnumbered by FODMAPs sensitivity in patients spontaneously adhering to GFD. Distinction between these 2 conditions is clinically relevant in relation to dietary counselling. References: 1 Ludvigsson et al . Gut 2013;62:43 2 Gibson and Muir. Gastroenteroloy 2013;145; 693 Disclosure of Interest: None Declared.